TO THE ANALYSIS OF STABILITY OF MOVEMENT OF THE NONLINEAR MECHANICAL SYSTEMS - Kydyrbekuly, A.B. (Recent Contributions to Physics, 2008)
Stability of movement of nonlinear mechanic systems with nonlinear characteristics of various types is considered. The technique of research of dynamic stability of nonlinear systems on Lyapunov is offered. It is building on the task of the equation of the indignant condition of system the parametrical equation of type Hill and the definition a characteristic determinant by method Flock.